AKAL DALAM PERSPEKTIF HADITS TARBAWI SEBAGAI LANDASAN PENDIDIKAN ISLAM - Maslani, Maslani; Fitriya, Erma; Rosulina, Desi; Munawaroh, A.H. Eviyani; Koswara, Ujang (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
This paper discusses the education of reason in the Islamic perspective, focusing on the concept of education of reason as taught in the hadiths of the Prophet Muhammad. The objectives of this study are to understand the meaning of education of reason, to analyse the hadiths related to education of reason, and to explore the relationship between education of reason and character development in the context of the Project for Strengthening the Profile of Pancasila Students and the Profile of Rahmatan lil Alamin Students (P5-PPRA). This study uses a qualitative approach with a literature study method, in which an analysis is carried out on various literature, hadiths, and opinions of scholars related to education of the mind. The results show that education of the mind in Islam includes the development of intellectual and spiritual abilities. Education of the mind not only aims to improve rational and critical thinking abilities, but also to shape individuals who are faithful, have good character, and have a balance between worldly and spiritual knowledge. In the context of P5-PPRA, education of the mind plays a role in producing students who are not only intelligent but also capable of behaving well and contributing positively to society. This study confirms that an education of the mind based on Islamic principles has a significant impact on developing children's intellect and character. ABSTRAKArtikel ini membahas tentang pendidikan akal dalam perspektif Islam, dengan fokus pada konsep pendidikan akal yang diajarkan dalam hadis-hadis Nabi Muhammad SAW. Tujuan dari penelitian ini adalah untuk memahami makna pendidikan akal, menganalisis hadis-hadis yang berkaitan dengan pendidikan akal, dan mengeksplorasi hubungan antara pendidikan akal dan pengembangan karakter dalam konteks Proyek Penguatan Profil Mahasiswa Pancasila dan Profil Mahasiswa Rahmatan lil Alamin (P5-PPRA). Penelitian ini menggunakan pendekatan kualitatif dengan metode studi literatur, di mana dilakukan analisis terhadap berbagai literatur, hadis, dan pendapat para ulama yang berkaitan dengan pendidikan akal. Hasil penelitian menunjukkan bahwa pendidikan akal dalam Islam mencakup pengembangan kemampuan intelektual dan spiritual. Pendidikan akal tidak hanya bertujuan untuk meningkatkan kemampuan berpikir rasional dan kritis, tetapi juga untuk membentuk individu yang beriman, berakhlakul karimah, dan memiliki keseimbangan antara pengetahuan duniawi dan ukhrawi. Dalam konteks P5-PPRA, pendidikan budi berperan untuk menghasilkan peserta didik yang tidak hanya cerdas, tetapi juga mampu berperilaku baik dan berkontribusi positif bagi masyarakat. Penelitian ini menegaskan bahwa pendidikan akal yang berlandaskan prinsip-prinsip Islam memiliki dampak yang signifikan dalam mengembangkan kecerdasan dan karakter anak.